Identification of genomic loci associated with genotypic and phenotypic variation among Pseudomonas aeruginosa clinical isolates from pneumonia - Mesquita, Cristina S (2019)
In this work, a genotype-phenotype survey of a highly diversified Pseudomonas aeruginosa collection was conducted, aiming to detail pathogen-associated scenarios that clinicians face nowadays. Genetic relation based on RAPD-PCR of 705 isolates, retrieved from 424 patients and several clinical contexts, reported an almost isolate-specific molecular-pattern. Pneumonia-associated isolates HB13 and HB15, clustered in the same RAPD-PCR group, were selected to evaluate the genomic background underlying their contrasting antibiotic resistance and virulence. The HB13 genome harbors antibiotic-inactivating enzymes-coding genes (e.g. aac(3)-Ia, arr, blaVIM-2) and single-nucleotide variations (SNVs) in antibiotic targets, likely accounting for its pan-resistance, whereas HB15 susceptibility correlated to predicted dysfunctional alleles. Isolate HB13 showed the unprecedented rhl-cluster absence and variations in other pathogen competitiveness contributors. Conversely, HB15 genome comprises exoenzyme-coding genes and SNVs linked to increased virulence. Secretome analysis identified signatures features with unknown function as potential novel pathogenic (e.g. a MATE-protein in HB13, a protease in HB15) and antibiotic resistance (a HlyD-like secretion protein in HB13) determinants. Detection of active prophages, proteases (including protease IV and alkaline metalloproteinase), a porin and a peptidase in HB15 highlights the secreted arsenal likely essential for its virulent behavior. The presented phenotype-genome association will contribute to the current knowledge on Pseudomonas aeruginosa pathogenomics.